Diseño de un sistema de gestión ambiental basado en la norma iso-14001 para las empresas productoras de cebolla larga en el municipio de Aquitania (Boyacá) (2023)
The purpose of this research is the design of an environmental management system based on ISO 14001:2015, developed for ASOPARCELA. This design allows the prevention of pollution and environmental impacts derived from the processes for the production of onion in the municipality of Aquitania (Boyacá). With the passage of time business needs have evolved, the environmental part is now an important part for the development of any organization, therefore, they are in constant search of a balance between the economic, social and now in environmental responsibility, which is summarized in a whole set of areas that must interact with each other to achieve quality processes, so that these different areas can continuously improve hand in hand with each other and that organizations can prevail despite the competition, The municipality of Aquitania has a very important natural resource at the national level, Lake Tota, which provides the water resource necessary for the production of the onion, and it has been increasingly negatively affected because the organizations do not have the necessary knowledge to adopt processes that can mitigate the negative environmental impact caused to it since this productive activity has been developed. For this reason, taking as a reference the ISO 14001 standard, we proceeded to design the environmental management system for the relevant use of ASOPARCELA, where an initial diagnosis was made in order to collect important information for the development of the same and proceeded to design the entire operational and documentary system necessary for the proper implementation of the environmental management system